Kesejahteraan Nelayan Puger Jember Perspektif Maqashid Syariah Al-Syatibi - Fajar Kristanto; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The goal of the title is to find out how Puger Wetan fishermen welfare in maqashid syariah Al-Syatibi indicator. There is five indicators among them is religion, life, hereditary, mind, and wealth. Hence, there is three stages in maqashid syariah. First level is dharuriyyat, that should be safe-guardes, comfort or happiness named hajiyyat level, and luxury named tahsiniyyat level. The research methodology is explanative qualitative with case study. Data was collected through interviews where the informants in this study is Puger’s FKKUBN secretary, Big boat fishermen, jukung boat fisherman, the crew, respected old fishermen, and Puger Wetan village official. The second data was collected through journals, books, BPS, vilage’s data, internet access, and other literature. The result of this study is that fishermen in Puger Wetan village are not prosperous because they are failed in fulfilling the maqashid syariah indicator at the dharuriyyat level, namely wealth. The existence of fishermen's assets is included in riba qardh because the system of accounts payable between fishermen and pengambek (investors) requires additional benefits in the accounts payable agreement. As a result of the debt agreement above, the process of market balance has never happened because the price is in the hands of pengambek, so buying and selling activities at Puger’s TPI are not auctioned and the market is not running as it should. In the future, the above asset indicators can be improved by changing the debt agreement to become a mudharabah contract. However, the solution provided by the researcher can be practiced if the pengambek is also roomy and also aware that the system has been detrimental to fishermen and is committed to improving the welfare of fishermen in Puger Wetan villageKeywords: Maqashid Syariah, Al-Syatibi, Fishermen Welfare, PengambekThe goal of the title is to find out how Puger Wetan fishermen welfare in maqashid syariah Al-Syatibi indicator. There is five indicators among them is religion, life, hereditary, mind, and wealth. Hence, there is three stages in maqashid syariah. First level is dharuriyyat, that should be safe-guardes, comfort or happiness named hajiyyat level, and luxury named tahsiniyyat level. The research methodology is explanative qualitative with case study. Data was collected through interviews where the informants in this study is Puger’s FKKUBN secretary, Big boat fishermen, jukung boat fisherman, the crew, respected old fishermen, and Puger Wetan village official. The second data was collected through journals, books, BPS, vilage’s data, internet access, and other literature. The result of this study is that fishermen in Puger Wetan village are not prosperous because they are failed in fulfilling the maqashid syariah indicator at the dharuriyyat level, namely wealth. The existence of fishermen's assets is included in riba qardh because the system of accounts payable between fishermen and pengambek (investors) requires additional benefits in the accounts payable agreement. As a result of the debt agreement above, the process of market balance has never happened because the price is in the hands of pengambek, so buying and selling activities at Puger’s TPI are not auctioned and the market is not running as it should. In the future, the above asset indicators can be improved by changing the debt agreement to become a mudharabah contract. However, the solution provided by the researcher can be practiced if the pengambek is also roomy and also aware that the system has been detrimental to fishermen and is committed to improving the welfare of fishermen in Puger Wetan villageKeywords: Maqashid Syariah, Al-Syatibi, Fishermen Welfare, Pengambek1 Jurnal ini merupakan bagian dari skripsi Fajar Kristanto, NIM: 041311433005, yang diuji pada tanggal 16 Mei 2019.I. PENDAHULUANTujuan hidup manusia adalah mencapai kesejahteraan, meskipun setiap orang memiliki definisi yang berbeda-beda mengenai kesejahteraan. Sebagian besar pakar ekonomi mendefinisikan kesejahteraan sosial adalah pemenuhan kebutuhan hidup di dunia dan segala sesuatu yang mendukungnya. Todaro (2003) menjelaskan, “Kesejahteraan masyarakat menengah ke bawah dapat direpresentasikan dari tingkat hidup masyarakat. Tingkat hidup masyarakat ditandai dengan terentaskanya REFERENCESBakri, Asafri Jaya. 1996. Konsep Maqashid Syariah Menurut Al-Syatibi. Jakarta: Raja Grafindo Persada.Kasdi. Abdurrahman. 2014. Maqasyid Syari’ah Perspektif Pemikiran Imam Syatibi dalam Kitab Al-Muwafaqat. Jurnal YUDISIA Vol 5 : 46-62.Riyadi dkk. 2015. Indikator Kesejahteraan Rakyat 2015. Jakarta : BPS-Statistics Indonesia.Ryandono, Muhamad Nafik Hadi dan Moh. Qudsi Fauzy. 2015. Pengembangan Model Fungsi Sosial Bisnis Islam Berdasarkan Maqashid Syariah pada Bank Syariah X. Jurnal Telaah Bisnis Vol 16 : 31-46.Herianingrum, Sri. 2014. Implementation of Maqashid al Sharia as a Model of Economic Development Agriculture in East Java. Jurnal Academic Star of Business and Economics. Vol 5 : 1701-1708.Ahmad, Norashikin dan Mohd Shukri Hanapi. 2018. Maqashid al-Syariah Thought in Mainstream Islamic Economics: A Review. International Journal of Academic Research in Business and Social Sciences Vol 8 : 626-636.Adiba, Elfira Maya dan Atina Shofawati. The Role of Middlemen and Fishermen Welfare in Maqashid Shariah Perspective. Jurnal Islamic Economics Science Vol 1 : 1-14.Kara, Muslimin. 2012. Pemikiran Al-Syatibi Tentang Maslahah dan Implemetasi dalam Pengembangan Ekonomi Syariah. Jurnal ASSETS Vol 2 : 173-183.Harahap, Zul Anwar Ajim. 2014.Konsep Maqasid Al-Syariah sebagai Dasar dan Penerapanya Dalam Hukum Islam Menurut ‘Izzudin Bin‘ Abd Al-Salam (W.660H). Jurnal Tazkir Vol.9 : 171-189.Muzlifah, Eva. 2013. Maqashid Syariah Sebagai Paradigma Dasar Ekonomi Islam. Jurnal Ekonomi dan Hukum Islam Vol 3 : 73-92.Pusparini, Martini Dwi. 2015. Konsep Kesejahteraan dalam Ekonomi Islam. Jurnal Ekonomi Islam Vol 1 : 45-59.Purnomo, Agus. 2015. Islam dan Konsep Welfare State dalam Ekonomi Islam. Jurnal Al-Iqtishadiyah : 99-109.Kholis, Nur. 2015. Kesejahteraan Sosial di Indonesia Perspektif Ekonomi Islam. Jurnal AKADEMIKA Vol 20 : 243-260.Widiastuti, Tika. Kesejahteraan dan Kemiskinan dalam Perspektif Islam. IR-Universitas Airlangga Surabaya : 1-54.Djalaluddin, Muhammad Mawardi. 2015. Pemikiran Abu Ishaq Al-Syatibi dalam Kitab Al-Muwafaqat. Jurnal Al-Daulah Vol 4 : 289-300.Amin, Mahir. 2014. Konsep Keadilan dalam Perspektif Filsafat Hukum Islam. Jurnal Al-Daulah Vol 4: 322-342.Ahmadi, Imam, Hariyono dan Siti malikah Thowaf. Puger: Sejarah dan Potensi Ekonomi. Makalah.Triyanti, Riesti dan Maulana Firdaus. 2016. Tingkat Kesejahteraan Nelayan Skala Kecil dengan Pendekatan Penghidupan Berkelanjutan Di Kabupaten Indramayu. Jurnal Sosek KP Vol 11 : 29-43.Djamil, Fathurrahman. 2017. Mencari Format Hukum Islam yang Progresif Berkearifan Lokal : Pendekatan Sosio-Cultural dan Maqashid Syariah. Jurnal Kordinat Vol 16 : 1-13.Gemaputri, Ariesia A. Gemaputri. 2013. Tingkat Pemanfaatan Sumber Daya Ikan Hasil Tangkapan di Perairan Jember. Jurnal Perikanan (J.Fish. Sci.) Vol 15 : 35-41.Koordinator Statistik Kecamatan Puger Kabupaten Jember. 2016. Kecamatan Puger dalam Angka 2016. Jember : Badan Pusat Statistik Kabupaten JemberKoordinator Statistik Kecamatan Puger Kabupaten Jember. 2017. Kecamatan Puger dalam Angka 2017. Jember : Badan Pusat Statistik Kabupaten JemberKoordinator Statistik Kecamatan Puger Kabupaten Jember. 2018. Kecamatan Puger dalam Angka 2018. Jember: Badan Pusat Statistik Kabupaten JemberFitriyah, Khirul dan Djoko Widodo. Karakteristik Sosial Budaya dan Ekonomi Nelayan Kecil di Wilayah Pesisir Desa Puger Wetan Kecamatan Puger Kabupaten Jember. Makalah.Mumtahiyah. 2015. Implementasi Profesi Nelayan Muslim dalam Mewujudkan Kesejahteraan Perspektif Maqashid Syariah Studi Kasus Nelayan Muslim Kabupaten Jembrana Bali. Tesis. Universitas Airlangga.https://regional.kompas.com/read/2018/11/16/12171421/umk-jatim-2019-ditetapkan-tertinggi-rp-38-juta-terendah-rp-17-juta diakses 13 April 2019, 20.29 WIB.